Soliton radiation beat analysis of optical pulses generated from two continuous-wave lasers - Zajnulina, M. (2015)
We propose a fibre-based approach for generation of optical frequency combs (OFC) with the aim of calibration of astronomical spectrograph in the low and medium-resolution range. This approach is based on two steps: in the first step, an appropriate state is generated and subsequently moulded in the second step into the desired OFC. In the system we propose, the first step is realised by injection of two continuous-wave (CW) lasers into a conditional single-mode fibre, whereas the second step generates a broad OFC by using the optical solitons generated in step one as initial condition. We investigate the conversion of a bichromatic input wave produced by two initial CW lasers into a train of optical solitons which happens in the fibre used in step one. Especially, we are interested in the soliton content of the pulses created in this fibre. For that, we study different initial conditions (a single cosine-hump, an Akhmediev breather, and a deeply-modulated bichromatic wave) by means of Soliton Radiation Beat Analysis and compare the results to draw conclusion about the soliton content of state generated during the first step.